Comparison of Feed Intake, Blood Metabolic Parameters, Body and Organ Weights of Growing Broilers Originating from Dwarf and Standard Broiler - Tona, K.; Onagbesan, O.M.; Bruggeman, V.; Mertens, K.; Jego, Y.; Decuypere, E. (International Journal of Poultry Science, 2004)
Growing broilers from three female breeder lines were compared to determine the relationship between feed intake, body weights, relative growth (RG), blood triiodothyronine (T3) and carbon dioxide partial pressure (pCO2) levels, heart and liver ratio to body weights in order to establish the dynamics of growth at different periods during rearing. The lines included a standard heavy S line, an experimental (E) line and a Label-type line (L). The E and L lines breeders carry the sex-linked dwarfing `dw` gene and are being used to assess the potential for the `dw` gene to reduce feed intake or lower feed restriction to improve reproductive performance in heavy female broiler parent stock. Four incubation settings, each of 2 replications of 150 eggs /line (total of 3,600 eggs) were incubated. At the end of each incubation setting, samples of chicks were reared in order to record broiler body, heart and liver weights, and to measure thyroid hormone levels and gas pressure in blood during specific periods of growth namely at d 14, 28 or 41 of age. The results showed that although broiler body weights at 14, 28 and 41 d were different between lines (S > E > L) at these times, only the RG during the periods 1-14 d and 15-28 d were different between lines. The RG decreased sharply with increasing age of broilers depending on the lines but become similar during the period of 28 to 41 d. On the contrary, feed intake increased with the age of broilers. Feed conversion ratio (FCR) decreased with age but not different between lines. Heart and liver ratios to body weights as well as pCO2 levels followed the same trend as RG in relation to the age of broilers and the lines. The levels of T3 also decreased with increasing age of broilers but at each age these levels were similar between lines. These data suggest a logical positive correlation between T3, pCO2, FCR, heart and liver ratios to RG at different stages of growth depending on the lines. It is concluded that selection for fast growth improved broilers growth mainly during the first 4 weeks of rearing in the S line; the dwarf lines also showed high growth during the same period with a higher rate in the E line. The results suggest that heavy broiler production may benefit from the use of the dw E line from the viewpoint of lower feed consumption in both the parent stock and the broilers combined with the higher reproductive performance of the parent stock.